Espionage in ancient civilizations (3000BC-757AD) - Abdullah, Hassan Togun; Sajit, Adnan Maleh; Hassan, Marwa Habib (Journal of Humanities & Social Sciences, 2021)
The work of espionage was known since the rise of the first human civilizations, which resulted in the emergence of the first state in the world, which was in Egypt, Iraq, Greeks, Romans, Persians, and Chinese, and all other world civilizations followed suit. Prophets also used espionage and also the Arabs before Islam. The espionage operations that some historical sources have dealt with for a period of three or four thousand years past are not only rare, but they do not easily disclose their secrets and do not address the subject in explicit terms, so we have to look for them in hidden references in the pages of history and through the importance that emerged from the methods of espionage that were in Ancient civilizations and the answer to the research questions that included how espionage was, when it was valuable, and who are the spies. It was imposed as a result of the political and military developments at the time, in addition to that, the importance of helping to stabilize the internal situation of the state. For rulers to know the most accurate news related to the affairs of their subjects or enemies. Finally, the researcher recommends the need to study espionage in the Indian and Phoenician civilizations.